Significance of predicted future liver remnant volume on liver failure risk after major hepatectomy: a case matched comparative study - Piccus, R.; Joshi, K.; Hodson, J.; Bartlett, D.; Chatzizacharias, N.; Dasari, B.; Isaac, J.; Marudanayagam, R.; Mirza, D. F.; Roberts, J. K.; Sutcliffe, R. P. (Frontiers in Surgery, 2023)
Introduction Future liver remnant volume (FLRV), a risk factor for liver failure (PHLF) after major hepatectomy (MH), is not routinely measured. This study aimed to evaluate the association between FLRV and PHLF. Patients and methods All patients undergoing MH (4+ segments) between 2011-2018 were identified from a prospectively maintained single-centre database. Perioperative data were collected for patients with PHLF, who were matched (1:2) with non-PHLF controls. FLRV and FLRV% (i.e. % of total liver volume) were calculated retrospectively from preoperative CT scans using Synapse- 3D software, and compared between the PHLF and matched control groups. Results Of 711 patients undergoing MH, PHLF occurred in 27 (3.8%), of whom 24 had preoperative CT scans available. These patients were matched to 48 non-PHLF controls, 98% of whom were classified as being at high risk of PHLF on preoperative risk scoring. FLRV% was significantly lower in the PHLF group, compared to matched controls (median: 28.7 vs. 35.2%, p=0.010), with FLRV% < 30% in 58% and 29% of patients, respectively. Assessment of the ability of FLRV% to differentiate between PHLF and matched controls returned an area under the ROC curve of 0.69, and an optimal cut-off value of FLRV% < 31.5%, which yielded 79% sensitivity and 67% specificity. Conclusions FLRV% is significantly predictive of PHLF after MH, with over half of patients with PHLF having FLRV% < 30%. In light of this, we propose that all patients should undergo risk stratification prior to MH, with the high risk patients additionally being assessed with CT volumetry.